Tournaments: There Is More Than Meets the Eye - Gil S. Epstein; Shmuel Nitzan (Institute for the Study of Labor (IZA), 2004)
By the well established tournament literature, incomplete information regarding the employees? productivity is essential for the rationalization of (efficiency-enhancing) tournaments. In this paper we propose an alternative rationalization of tournaments focusing on a fully informed principal whose objective is to maximize a weighted average of the profitability (productivity) of his team and of the promotion-seeking efforts of his employees. Our first main result clarifies the conditions under which the principal has an incentive to create a tournament that determines the promoted employee. We then examine the effect of the employees' productivity on their probability of promotion and on the extent of the resources wasted in the tournament. In particular, we specify the conditions that ensure that the most productive employee (the natural candidate for promotion) is less likely to be promoted and the conditions under which higher employee's productivity results in increased wasted promotion-seeking efforts.
Keywords: J2; D71; D2; 330; tournaments; promotion; Agency Theory; Wettbewerb; Erwerbsverlauf; Theorie; Tournament